Comparison of continuous versus intermittent enteral nutrition in critically ill patients (COINN): study protocol for a randomized comparative effectiveness trial - Hrdy, Ondrej; Vrbica, Kamil; Strazevska, Eva; Suk, Petr; Souckova, Lenka; Stepanova, Radka; Sas, Igor; Gal, Roman (Trials, 2020)
BACKGROUND: Enteral nutrition is part of the treatment of critically ill patients. Administration of enteral nutrition may be associated with signs of intolerance, such as high gastric residual volumes, diarrhea, and vomiting. Clinical trials regarding the effects of the mode of administration of enteral nutrition on the occurrence of these complications have yielded conflicting results. This trial aims to investigate whether the mode of administration of enteral nutrition affects the time to reach nutritional targets, intolerance, and complications. METHODS: COINN is a randomized, monocentric study for critically ill adult patients receiving enteral nutrition. Patients will be randomly assigned to two groups receiving (1) continuous or (2) intermittent administration of enteral nutrition. Enhancement of enteral nutrition will depend on signs of tolerance, mainly the gastric residual volume. The primary outcome will be the time to reach the energetic target. Secondary outcomes will be the time to reach the protein target, tolerance, complications, hospital and ICU lengths of stay, and 28-day mortality. DISCUSSION: This trial aims to evaluate whether the mode of application of enteral nutrition affects the time to reach nutritional targets, signs of intolerance, and complications. TRIAL REGISTRATION: ClinicalTrials.gov NCT03573453. Registered on 29 June 2018.
Keywords: průjem; Humans; dospělí; Diarrhea; Critical care; lidé; Critical Illness; randomizované kontrolované studie jako téma; Vomiting; Adult; Intensive care unit; Enteral nutrition; jednotky intenzivní péče; Randomized Controlled Trials as Topic; Gastric residual volume; Enteral Nutrition; zvracení; kritický stav; Intensive Care Units; enterální výživa